2022
DOI: 10.5194/acp-2022-327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling Diurnal Variation of SOA Formation via Multiphase Reactions of Biogenic Hydrocarbons

Abstract: Abstract. The daytime oxidation of biogenic hydrocarbons is attributed to both OH radicals and O3, while nighttime chemistry is dominated by the reaction with O3 and NO3 radicals. Here, the diurnal pattern of Secondary Organic Aerosol (SOA) originating from biogenic hydrocarbons was intensively evaluated under varying environmental conditions (temperature, humidity, sunlight intensity, NOx levels, and seed conditions) by using the UNIfied Partitioning Aerosol phase Reaction (UNIPAR) model, which comprises mult… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…No significant impact of acidic seed on SOA formation appeared under similar experimental conditions. For example, non-seeded SOA growth is similar to SA-seeded SOA for theC10 alkane (i.e., C10A vs. C10B and C10C vs. C10D, respectively), suggesting that most alkane oxidation products are inert and less polar compared to other oxygenated products from biogenic (Yu et al, 2021;Beardsley and Jang, 2016;Han and Jang, 2022a) and aromatic HCs (Im et al, 2014;Han and Jang, 2022a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…No significant impact of acidic seed on SOA formation appeared under similar experimental conditions. For example, non-seeded SOA growth is similar to SA-seeded SOA for theC10 alkane (i.e., C10A vs. C10B and C10C vs. C10D, respectively), suggesting that most alkane oxidation products are inert and less polar compared to other oxygenated products from biogenic (Yu et al, 2021;Beardsley and Jang, 2016;Han and Jang, 2022a) and aromatic HCs (Im et al, 2014;Han and Jang, 2022a).…”
Section: Resultsmentioning
confidence: 97%
“…The UNIPAR model's ability to accurately simulate SOA formation from various aromatic HCs (Im et al, 2014;Han and Jang, 2022a), monoterpenes (Yu et al, 2021), and isoprene (Beardsley and Jang, 2016) has been previously demonstrated. In this study, the UNIPAR model was extended to simulate the formation of SOA from multiphase reactions of linear alkanes including gas (g), organic (org), and inorganic (inorg) phases.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The vital source of NO 3 is the decomposition of N 2 O 5 via a thermodynamic equilibrium reaction to form NO 2 and NO 3 . In the presence of aqueous aerosol, N 2 O 5 reacts with water forming HNO 3 , which significantly reduces the concentration of NO 3 . Therefore, the contribution of NO 3 might be insignificant for the MC-LR decay in ambient air.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…In the presence of aqueous aerosol, N 2 O 5 reacts with water forming HNO 3 , which significantly reduces the concentration of NO 3 . 57 Therefore, the contribution of NO 3 might be insignificant for the MC-LR decay in ambient air. The sulfur species, including SO 2 , H 2 S, and dimethyl sulfide, are emitted from anthropogenic fuel combustions and wetlands and produce sulfuric acid via homogeneous gas-phase reactions and heterogeneous aqueous reactions in the aerosol phase.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%